2020
DOI: 10.21106/ijma.429
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Prevention of Mother-to-Child Transmission of HIV Care into General Maternal Child Health Care in Western Kenya

Abstract: Background: Health systems integration is becoming increasingly important as the global health community transitions from acute, disease-specific health programming to models of care built for chronic diseases, primarily designed to strengthen public-sector health systems. In many countries across sub-Saharan Africa, including Kenya, prevention of mother-to-child transmission of HIV (pMTCT) services are being integrated into the general maternal child health (MCH) clinics. The objective of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A mentor mother program was also initiated in 2013 for counselling and peer-support of pregnant women living with HIV 6 . During the trial, beginning in 2015, PMTCT care was integrated with regular ANC care with the aim of decreasing HIV related stigma due to visiting HIV specific clinics 6 , 50 . Another study from Kenya observed improvements in the uptake of EID HIV testing after implementation of a mentor mother and defaulter tracing program to improve PMTCT care 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A mentor mother program was also initiated in 2013 for counselling and peer-support of pregnant women living with HIV 6 . During the trial, beginning in 2015, PMTCT care was integrated with regular ANC care with the aim of decreasing HIV related stigma due to visiting HIV specific clinics 6 , 50 . Another study from Kenya observed improvements in the uptake of EID HIV testing after implementation of a mentor mother and defaulter tracing program to improve PMTCT care 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the average cost per pregnant-infant (PPY) pair in the high HIV city ranges from 6,280 ETB (US$319) to 21,620 ETB (US$1,099), etc. [ 9 ]. There are also researchers who evaluated the effectiveness of the city government-led all-round multilevel cooperation platform model in blocking mother-to-child transmission of AIDS.…”
Section: Introductionsmentioning
confidence: 99%
“…AMPATH has enrolled over 200,000 patients and currently provides care for approximately 15,000 children who are HEU and HIV+ in 65 clinics in western Kenya ( 9 , 10 ). The children and their caregivers were recruited from the MTRH and AMPATH pediatric HIV clinics between 12/2017 and 9/2019, where care for prevention of mother-to-child transmission (PMTCT) of HIV has been freely provided since 2003 ( 11 ). Mixed convenience sampling of potential participants occurred within these clinics, with periods of consecutive sampling by study team members positioned within the clinic along with the clinic staff notifying the study team of eligible participants when the team was not physically present.…”
Section: Methodsmentioning
confidence: 99%